The Origin of Chinese Cultural Genes - Chen, Shengqian. author. aut Link
XI, 364 p. 54 illus., 50 illus. in color.
Keywords: This book first traces the evolution of Chinese culture, which has a triple structure. It traces back to the economic basis of the formation of Chinese culture and analyzes the pattern of the formation of Chinese civilization. The book goes deep into the level of cultural genes, explores the origin of Chinese culture, and discusses the construction of contemporary Chinese culture in combination with the general trend of historical process. Shengqian Chen is a professor and doctoral supervisor of the Department of Archaeology and Museum at the School of History, Renmin University of China. Born in Jiayu, Hubei in 1972. In 1993, he graduated from the School of Archaeology, Jilin University with a bachelor's degree. In 1996, he graduated from the Department of Archaeology of Peking University with a master's degree. In 1998, he went to the Southern Methodist University of the United States to study for a doctor's degree under Dr. Fred Wendorf, former president of Society for American Archaeology , and Dr. Lewis R. Binford, the leader of "New Archaeology". In 2004, he received a doctor's degree. His main research fields include archaeological theory, prehistoric archaeology, stone tools analysis, etc. His works include Prehistoric Modernization, Thinking Archaeology, Learning Archaeology, Human Questioning, etc., and his translations include In Pursuit of the Past: Decoding the Archaeological Record , Archaeology: Key Concepts, Thinking Small: Global Perspectives on Microlithization, etc.